CDK8-Novel Therapeutic Opportunities - Ingeborg Menzl; Agnieszka Witalisz-Siepracka; Veronika Sexl (MDPI AG, 2019)
Improvements in cancer therapy frequently stem from the development of new small-molecule inhibitors, paralleled by the identification of biomarkers that can predict the treatment response. Recent evidence supports the idea that cyclin-dependent kinase 8 (CDK8) may represent a potential drug target for breast and prostate cancer, although no CDK8 inhibitors have entered the clinics. As the available inhibitors have been recently reviewed, we focus on the biological functions of CDK8 and provide an overview of the complexity of CDK8-dependent signaling throughout evolution and CDK8-dependent effects that may open novel treatment avenues.